2016
DOI: 10.1039/c6ra08641a
|View full text |Cite
|
Sign up to set email alerts
|

Controlled biodegradation of polymers using nanoparticles and its application

Abstract: The disposal of non-degradable plastics is augmented exponentially as a result of poor recycling efficacy. The development of biodegradable plastics has become indispensable in last two decades because of its origin from renewable resources. The potential interest in biodegradable plastics involves eco-friendly obliteration via microbial action which transform into carbon dioxide and water resulting pollution free natural system. Even though its lucrative interest lies in multiple areas, some of the properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 198 publications
(193 reference statements)
1
33
0
Order By: Relevance
“…Thus, it can be concluded that the addition of MWCNT to the CS/PVA membranes results in the formation of membranes with higher biodegradability. This conclusion is confirmed by Kumar el al . They reported that good dispersion of fillers in the exfoliated nanostructure degrades the polymer more rapidly compared to the pure membrane …”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, it can be concluded that the addition of MWCNT to the CS/PVA membranes results in the formation of membranes with higher biodegradability. This conclusion is confirmed by Kumar el al . They reported that good dispersion of fillers in the exfoliated nanostructure degrades the polymer more rapidly compared to the pure membrane …”
Section: Resultssupporting
confidence: 61%
“…This conclusion is confirmed by Kumar el al. 48 They reported that good dispersion of fillers in the exfoliated nanostructure degrades the polymer more rapidly compared to the pure membrane. 48…”
Section: Biodegradabilitymentioning
confidence: 99%
“…The dominant physicochemical properties of TiO 2 nanostructures are classi-ed in terms of their crystallinity, purity, structure, chemical composition, size-and/or shape-distribution, dimensionality and defect centres, which can be easily modied by changing the parameters during various synthetic methods. TiO 2 nanostructures have been widely explored owing to their extensive applications across a myriad of areas, particularly in photocatalysis, including those for the decomposition of organic/ inorganic dyes, 16,23,[36][37][38][39][40] hydrogen production from water, [41][42][43][44] removal of pollutants and plastics from the environment, [45][46][47][48] dye-sensitized solar cells, 49 sensors, 50 sunscreens, [51][52][53][54] paints, 55,56 rechargeable batteries, [57][58][59] supercapacitors, 60 food colouring, [61][62][63][64] environmental remediation and biomedical elds. 95,96 Over the past few decades, extensive research effort has been dedicated to the engineering of TiO 2 nanostructures synthesized via chemical routes, such as sol-gel, [97][98][99][100][101][102][103][104]…”
Section: Introductionmentioning
confidence: 99%
“…The products of enzymatic degradation and hydrolysis are the same, but the two pathways differ in the catalyst involved. The cleavage of ester bonds of APs is mediated by lipases, cutinases, serine proteases, PHB depolymerase, PCL depolymerase, elastase esterase, proteinase K, and trypsin [92]. Enzymatic degradation is therefore a heterogeneous process, which occurs via two steps of adsorption and hydrolysis.…”
Section: Enzymatic Degradationmentioning
confidence: 99%